Analisis Pengaruh Tunneling Incentive Pajak Dan Kepemilikan Asing Terhadap Penerapan Transfer Pricing Pada Perusahaan Lq45 Yang Terdaftar di Bei - Ninta Katharina (Jurnal Riset Akuntansi dan Bisnis, 2021)
Transfer pricing is the price in which products or services from a division are transferred to other divisions within the same company or between companies that have a special relationship. The purpose of this study is to determine and examine the effect of tunneling incentives, taxes and foreign ownership on the application of transfer pricing on LQ45 companies listed on the IDX for the period 2018-2020. The population in this study is the LQ45 companies listed on the BEI totaling 45 companies using the saturated method where all populations are sampled in the study. The method in this study uses 3 methods of analysis, namely classical assumption test, hypothesis testing and multiple linear regression test. The results of this study state that simultaneously, tunneling incentives, taxes and foreign ownership have a significant and significant effect on the implementation of transfer pricing in LQ45 companies listed on the IDX. Partially, foreign ownership and taxes can have a significant and significant effect on the implementation of transfer pricing on LQ45 companies listed on the IDX, while tunneling incentives have no and significant effect on the implementation of transfer pricing on LQ45 companies listed on the IDX.